HUBUNGAN PRAKTEK PEMBERIAN MP-ASI DINI DI KELUARGA DENGAN PERTUMBUHAN DAN PERKEMBANGAN PADA ANAK DIBAWAH USIA 3 TAHUN DI WILAYAH KERJA PUSKESMAS SAWAH LEBAR KOTA BENGKULU TAHUN 2012 - Malini, Nella; Wahyuni, Elly (JURNAL MEDIA KESEHATAN, 2012)
Growth and development has increased rapidly at an early age, from 0 to 5 years. This period is often referred to as the phase of the "Golden Age". Golden age is a very important time to pay attention to child development carefully in order to be detected as early as possible in case of abnormality. Impaired growth at the beginning of the baby's life was caused by malnutrition as a baby, giving complementary feeding too early or too late (MOH, 2005) to determine the relationship of giving early complementary feeding with growth and development in children under 3 years of age. The study design used in this study is the Survey Analytics, using a "Cross-sectional" where research is used to examine the relationship giving early complementary feeding on the growth and development of toddlers by using the approach of observation research (collecting data) is done once and within the same (time point approach). The population in this study were all children under the age of 3 years working inSawah Lebar Clinic, amounting to 90 people. The sample used in this study is the total sampling, sampling method is a door to door.The result showed that the majority of mothers giving complementary feeding early, almost all children have abnormal growth, more than most children have abnormal development, there is a correlation between the provision of complementary feeding with Growth Early child under 3 years of age and there is a relationship between giving the MP-ASI Early child Development under the age of 3 years. Suggestion: For health workers specially for Midwives to give education about the importance of monitoring the growth and development of toddlers because this period is often referred to as the phase of "Golden Age".